Morphometric Study of Nose of Three Ethnic Groups of Rural Population of Jumla, Nepal - Prasad, Ram Jiban; Thakur, Umeshwor Prasad; Marasini, Surendra; Bhushal, Kumar; Mishal, Jyoti; Shrestha, Subina; Amit, Arunendra Kumar (Nepal Journal of Health Sciences, 2026)
Introduction: The nose is one of the most important structures in the face, with both bones and cartilage, and performs a major function in smell and has profound aesthetic value as well. The study aims to provide baseline data of the nasal index of Nepalese people of high mountainous regions and to assess racial and gender variation between indigenous and non-indigenous groups, which will be of clinical and surgical interest in rhinology and craniofacial prosthetic and aesthetic purposes.Method: This was a descriptive cross-sectional study carried out among the residents of Jumla district aged 20-60 years with various ethnicities. A data gathering form with information including age, ethnicity, gender, and other useful personal bio-data was filled out for each subject. Nasal widths and lengths were measured with the aid of a manual spreading vernier caliper.Results: There were 386 participants from different ethnic groups, of which 192 were male and 194 were female. The mean nasal length of the male and the female were 42.96 ± 3.84 and 41.84 ± 3.51, and breadth were 34.02 ± 2.73 and 33.64 ± 2.58, respectively. Similarly, mean nasal index in males and females was 79.52 ± 6.20 and 80.78 ± 7.27.Among the total participants, 134 were Chhetri, 120 were Brahmin, and 132 were Dalit. The mean nasal breadth of the Brahmin, Chhetri, and Dalit were 34.71±2.59, 33.86±2.40, and 33.01±respectively. Similarly, the mean nasal length of the Brahmin, Chhetri, and Dalit were 43.95±3.76, 42.91±3.30, and 40.47± respectively. The mean nasal index of the Brahmin, Chhetri, and Dalit were 79.32±6.70, 79.23±6.83, and 81.85±7.07respectively.Conclusion: There was sexual dimorphism observed. The ethnic group Dalit had higher values. All the ethnic groups, including males and females, have had a similar type of nose, i.e. Mesorrine in the present study.